An innovative multi-modal retinal imaging system for in vivo retinal detection in small animals - Tang, Zhengyuan; Zhao, Tianze; Ren, Ji; Zhang, Kuan; Yin, Qi; Zhang, Teng; Zhang, Hui; Dong, Tianyu; Zhang, Pengfei; Zhang, Jie (Frontiers in Ophthalmology, 2023)
This paper presents an innovative retinal imaging system tailored for in vivo fundus detection in small animals. This system integrates Scanning Laser Ophthalmoscopy (SLO) and optical Coherence Tomography (OCT) techniques, enabling the simultaneous generation of images from various modalities, including SLO reflectance, SLO fluorescein angiogram, OCT, and OCT angiogram. The existing multi-modal retinal imaging systems generally encounter limitations such as the inability to detect peripheral lesion areas attributed to small Field of View (FOV) design and susceptibility to sample motion due to slow data acquisition speed. To address these challenges, it’s essential to underscore that this proposed system offers a range of notable advantages, including its compact design, the capacity for widefield imaging with a FOV of up to 100°, and a rapid OCT A-scan rate of 250 kHz, notably exceeding the capabilities of pre-existing multi-modal retinal imaging systems. Validation of the system involved imaging the eyes of normal wild-type mice and diseased mice afflicted with retinal detachment and choroidal neovascularization (CNV). The favorable imaging results demonstrate the system’s reliability in identifying retinal lesions in small animals.